Effects of heave motion on the dynamic performance of vertical transport system for deep sea mining. (August 2020) - Wu, Qi; Yang, Jianmin; Lu, Haining; Lu, Wenyue; Liu, Lei
Abstract: A deep sea mining system has been proposed as a way to overcome a future shortage of resources. A vertical transport system (VTS), as the key component for deep sea mining, is used between the surface vessel and the sea miner to convey minerals to the sea level. The objective of this paper is to investigate the effects of the heaving motion of the surface vessel on the dynamic response of a VTS. First, a VTS with a hybrid pipe composition for deep sea mining is introduced. A non-linear finite element method (FEM) is used to solve the governing equations of a VTS containing a time-dependent coefficient in the time domain. Three response scenarios are distinguished and analysed using examples. As the heaving amplitude or frequency increases, the VTS will first transform from a steady state into a transition state, and local dynamic buckling state will then occur. A response analysis of the buffer motion, the bending stress of a rigid pipe, and loads on the miner shows that the local dynamic buckling is the worst case in terms of structural safety.